Dipole response of the odd-proton nucleus 205Tl up to the neutron-separation energy. (17th October 2016) - Benouaret, N; Beller, J; Pai, H; Pietralla, N; Ponomarev, V Yu; Romig, C; Schnorrenberger, L; Zweidinger, M; Scheck, M; Isaak, J; Savran, D; Sonnabend, K; et al.
Abstract: The low-lying electromagnetic dipole strength of the odd-proton nuclide 205 Tl has been investigated up to the neutron separation energy exploiting the method of nuclear resonance fluorescence. In total, 61 levels of 205 Tl have been identified. The measured strength distribution of 205 Tl is discussed and compared to those of even–even and even–odd mass nuclei in the same mass region as well as to calculations that have been performed within the quasi-particle phonon model.